Laparoscopic Distal Pancreatectomy for a Pancreatic Lymphoepithelial Cyst: Case Report and Review of Literature - Yanagimoto, Hiroaki; Satoi, Sohei; Toyokawa, Hideyoshi; Yamamoto, Tomohisa; Hirooka, Satoshi; Yui, Rintaro; Yamaki, So; Yoshida, Kazumasa; Wada, George; Okuno, Masashi; et al. (JOP. Journal of the Pancreas, 2013)
Context Lymphoepithelial cysts of the pancreas are a rare disease of true pancreatic cysts, the cause of which is unknown. The differential diagnosis is broad and includes many benign and malignant cystic lesions of the pancreas and surrounding organs. A combination of imaging modalities and fine needle aspiration might narrow the differential diagnosis. However, the final diagnosis can only be achieved with certainty after resection of the cyst. Case report The present case report is a lymphoepithelial cyst of the pancreas that was resected laparoscopically. A 53-year-old man was incidentally found to have a cystic tumor in the tail of the pancreas after undergoing an abdominal ultrasound, which showed a 41x33 mm cystic mass in the pancreatic tail. He had no abdominal symptoms. Laparoscopic distal pancreatectomy and splenectomy were performed. Histologic examination revealed a lymphoepithelial cyst. Conclusion Herein, we discuss the diagnostic difficulties and management decisions that face surgeons treating pancreatic cysts. Image: Pancreatic lymphoepithelial cyst.